Mechanisms of EMT in the immune microenvironment of plasma cell mastitis - Zhou, Meng; Zhang, Yubi; Shao, Yuanhao; Wu, Bin; Zhou, Jing (Frontiers in Immunology, 2025)
Plasma cell mastitis (PCM), a prevalent and refractory form of non-lactating mastitis, is characterized by the pathological triad of ductal ectasia (DE), plasma cell-dominated inflammatory infiltration, and progressive fibrosis. Despite its clinical burden, current surgical interventions yield suboptimal outcomes with recurrence rates up to 43%, underscoring an urgent need for mechanistic insights. This review synthesizes evidence establishing epithelial-mesenchymal transition (EMT) as a central driver of PCM pathogenesis, intricately regulated by the disease-specific immune microenvironment. We demonstrate that autoimmune-mediated DE initiates ductal damage, generating damage-associated molecular patterns (DAMPs) that activate pattern recognition receptors (PRRs). This triggers NF-κB signaling hubs, upregulating pro-inflammatory mediators (IL-1β, IL-6, TGF-β1, ICAM-1, CXCL12) and core EMT-transcription factors (Snail, TWIST). Crucially, IL-6/JAK/STAT3 signaling promotes plasma cell survival via Bcl-2 while concurrently driving EMT in ductal epithelium. Concurrently, IL-1βactivate PI3K/Akt to stabilize EMT effectors and enhance ECM synthesis. A unique, self-amplifying “EMT-fibrosis loop” is identified as a PCM hallmark: EMT-derived fibroblasts secrete CXCL12 and TGF-β1, which activate NF-κB pathways in adjacent epithelia to perpetuate EMT and ECM deposition. This loop, alongside sustained plasma cell activity via IL-6/STAT3/Bcl-2, underpins PCM’s chronicity and distinguishes it from other mastitides like granulomatous lobular mastitis (GLM). We further highlight exosomal involvement in CXCL12 transport and M1 macrophage polarization as amplifiers of inflammation and EMT. Targeting these convergent pathways (NF-κB, JAK/STAT3) or disrupting the EMT-fibrosis loop (e.g., via CXCL12/TGF-β1 inhibitors) represents a promising therapeutic strategy to mitigate fibrosis and recurrence. Future research must validate these mechanisms in human-relevant models and address critical gaps in bacterial-autoimmune interplay and temporal dynamics across PCM stages.